USE OF ARTIFICIAL INTELLIGENCE IN PRESCHOOL EDUCATION (American Journal of Interdisciplinary Research and Development, 2026)
The rapid digital transformation of the 21st century is bringing fundamental changes to all spheres, including education. As a result of the development of artificial intelligence (AI) technologies, new opportunities have emerged in the educational process such as strengthening individualized learning approaches, accurately analyzing children's developmental progress, providing methodological support to teachers, and creating an interactive learning environment. At the same time, the use of AI technologies in preschool education is not only a requirement of the modern era, but also an important tool that helps increase children's digital literacy from an early age.